Dengue Fever Prevention Strategy in Puuk Village, Pidie Regency, Aceh Province - Agustina, Rahmi; Dewi, Ervina; Diana, Novita; Azmi, Ulil (Unram Journal of Community Service, 2025)
This program aims to evaluate the effectiveness of community empowerment as a strategy for preventing Dengue Fever (DBD) in Puuk Village, Aceh. A mixed-method approach was applied, combining quantitative surveys with qualitative techniques such as focus group discussions and in-depth interviews. The intervention program included training, counseling, environmental clean-ups, and participatory workshops. Results showed a significant increase in community knowledge and awareness regarding DBD, accompanied by improved preventive behaviors such as eliminating mosquito breeding sites and using repellents. Cross-sectoral coordination between health workers, community leaders, and local organizations further enhanced program outcomes, although limited resources and uneven information access remained challenges. The findings highlight that participatory empowerment can effectively change health behaviors and reduce DBD risk. The study implies that this model could be replicated in other regions, emphasizing the importance of collaboration, innovation, and sustainability in community-based health interventions.